Glioblastoma Following Treated Medulloblastoma After 29 Years in the Posterior Fossa: Case Report and Review of Literature - Mesbahi, Tarek; Zaine, Hind; Mahazou Abdou, Ismaël; Chekrine, Tarik; Sahraoui, Souha; Karkouri, Mehdi; Lakhdar, Abdelhakim (Frontiers in Oncology, 2022)
Abstract: Glioblastoma multiforme (GBM) is a highgrade glioma that may be a rare complication of radiotherapy. We report a case of patient who was treated for medulloblastoma of the posterior fossa at the age of 27. 29 years after, at the age of 56 years, he presents a double location tumor supratentorial and in the posterior fossa. imaging features of supratentorial location are very suggestive of a meningioma. We operated the posterior fossa location, and it revealed a glioblastoma. Histologically the tumor cells exhibited characteristics of both GBM and rhabdoid tumor cells. Cases of GBM following medulloblastoma at the same place reported in the literature are very rare, and presenting rhabdoid characteristics are even rarer. This is the first case of the MB and GBM at the age of 27 and 56, respectively. The double location supratentorial probably meningioma and GBM of the posterior fossa 32 years after medulloblastoma is the only case reported in the literature. what to do in this case remains debated and there are no clear recommendations in the literature.